INFLUENCE OF FOLATE CYCLE MTHFR GENE POLYMORPHISM ON THE PROCESS OF FETUS DEVELOPMENT IN RESIDENTS OF THE REPUBLIC OF UZBEKISTAN - Yangibaeva D.T; Yuldasheva D.Y; Chorieva G.Z; Sadullaeva U.A (Scholar Express Journals, 2023)
According to recent studies, throughout the world congenital malformations occur in 5% of newborns, and it is estimated that 303,000 children dying from malformations during the first 4 weeks of life (WHO, 2016). Today, women's reproductive health of women is one of the most important medical and social problems. For the birth of healthy offspring, it is worth taking care of a medical genetic examination even before the conception of a child and before his birth. The most common cause of miscarriage in the early stages are genetic abnormalities (up to 70% of non-developing pregnancies before 6 weeks, 50% before 10 weeks and 5% after 12 weeks of pregnancy), all three causes (hormonal disorders, infections (30%) may be present simultaneously
Keywords: abnormalities; common; causes; medical